2021
DOI: 10.1002/iid3.347
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting upper airway control of NSAID‐exacerbated respiratory disease: A real‐world study of 167 patients

Abstract: Background Nonsteroidal anti‐inflammatory drug (NSAID) exacerbated respiratory disease (N‐ERD) is a triad with asthma, chronic rhinosinusitis with nasal polyps, and NSAID intolerance. Uncontrolled N‐ERD forms a major public health problem due to frequent and difficult‐to‐treat exacerbations and/or requiring putatively frequent endoscopic sinus surgeries (ESS). Our aim was to study factors affecting control of N‐ERD. Methods Retrospective patient record data (patient characteristics, prior sinus surgeries, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…CRSwNP patients with co-morbid asthma and/or NERD have an increased risk for recurrence and revision ESS, although these patients seem benefit from initial ESS 13,19,[25][26][27] . This may reflect a more severe disease, with usually co-morbid NERD, anosmia, Type 2 high eosinophilic inflammation, and a greater tendency of polyp re-growth 23,[28][29][30][31][32][33][34][35][36][37] . When performing SFS, Immunodeficiency or its suspicion showed also to one of the top ten predictors by all three classifiers.…”
Section: Discussionmentioning
confidence: 99%
“…CRSwNP patients with co-morbid asthma and/or NERD have an increased risk for recurrence and revision ESS, although these patients seem benefit from initial ESS 13,19,[25][26][27] . This may reflect a more severe disease, with usually co-morbid NERD, anosmia, Type 2 high eosinophilic inflammation, and a greater tendency of polyp re-growth 23,[28][29][30][31][32][33][34][35][36][37] . When performing SFS, Immunodeficiency or its suspicion showed also to one of the top ten predictors by all three classifiers.…”
Section: Discussionmentioning
confidence: 99%
“…However, discontinuation of this therapy hampers correct long-term evaluation and still questions its actual value ( 122 ). A recent retrospective study concluded that nasal polyp eosinophilia, the frequent need of oral corticosteroid courses and a history of recurrent CRSwNP surgery were consistent factors predicting uncontrolled N-ERD ( 123 ).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…It has been shown that extended ESS reduces symptom scores among patients with CRS ( 23 ) and the need for revision surgery compared with partial ESS ( 24 ). A recent study has shown that partial ethmoidectomy in patients with N-ERD increased the risk of revision surgery ( 25 ). Furthermore, recurrent ESS surgeries predicted uncontrolled N-ERD ( 25 ).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…A recent study has shown that partial ethmoidectomy in patients with N-ERD increased the risk of revision surgery ( 25 ). Furthermore, recurrent ESS surgeries predicted uncontrolled N-ERD ( 25 ). ESS reduces patients' symptoms reported in the SNOT-22 scores, and this effect is also objectively seen in improvement in nasal endoscopy and CT scans postoperatively in patients with N-ERD ( 26 ).…”
Section: Surgical Treatmentmentioning
confidence: 99%